Analisis Bilirubin Dan Albumin Pada Penderita TB Tahap Awal Pengobatan Dan Tahap Akhir Menjalani Pengobatan - Karol Octrisdey; Ni Made Susilawati; I Gede Putu Arnawa; Neiny Prisy Foekh (STIKes Ibnu Sina Ajibarang, 2023)
Pulmonary tuberculosis is a direct infectious disease caused by Mycobacterium tuberculosis. Most TB germs attack the lungs, but can also affect other body organs. Tuberculosis is spread by germs, so tuberculosis can be transmitted from one person to another when a sufferer coughs. To overcome this, WHO recommends a DOTS strategy, one of which is treatment. Tuberculosis treatment is given in packages in the form of Fixed Dose Combination Anti-Tuberculosis Drugs (OAT-KDT). It is feared that long-term TB treatment will cause side effects on the liver because OAT is hepatotoxic. This study aims to analyze albumin and bilirubin levels at the beginning of treatment and at the end of treatment. This research is called observational research because the researcher only observes the research subjects and looks for data related to the research without treating the research subjects. This type of research is a combination of documentation and observational studies with a cross-sectional study design (Cross Sectional Study), which can assess changes in liver function, in this case albumin and total bilirubin, from pulmonary TB sufferers at the beginning of treatment and at the end of treatment undergoing TB treatment. The sample in this study was 13 patients. The research results showed that the results of examinations for patients at the start of treatment: there were 10 respondents (76.9%) who had albumin levels that were included in the normal category, while the remaining 3 had low albumin levels. Examination results for patients at the start of treatment: there were 11 respondents (84.6%) who had bilirubin levels which were included in the normal category while the remaining 2 had high bilirubin levels. Examination results for patients at the end of treatment: there were 7 respondents (70%) whose albumin levels were included in the normal category while the remaining 3 had high albumin levels. Examination results for patients at the end of treatment: there were 8 respondents (80%) who had bilirubin levels which were included in the normal category while the remaining 2 had low bilirubin levels. The results of the difference test show that there is a difference in albumin at the beginning of treatment and at the end of treatment with a p value of 0.010 < 0.05. Meanwhile, the opposite result was obtained, namely that there was no difference in patient bilirubin levels at the beginning of treatment and at the end of treatment with p values of 0.312, 0.286 and 0.352 > 0.05, respectively.